Analysis of the Mediation Role of Career Adaptability In the Relationship Between Emotional Intelligence and Achievement Motivation For Generation Z Students in West Kalimantan - Ginting, Sunardi (Pandawan, 2022)
This research involves all students of Generation Z who study in West Kalimantan as a population. The questionnaire was designed in google-form and distributed using snowball sampling technique through WhatsApp, Telegram and Line social media, resulting in 6,721 responses. The selection process from the total responses decided 5,178 respondents were eligible and fit the research targets, while 1,543 others were dropped because some were studying outside West Kalimantan and some were still in high school. The age of the respondents spread from 19 to d. 23 years old and by gender, 1,890 of them were male and 3,288 were female. The campuses where they study are spread out at Tanjungpura University, Widya Dharma University, IKIP PGRI, Polnep, Panca Bhakti University, Kapuas Sintang University, Muhamadyah University and other campuses in West Kalimantan. The collected data was processed using WarpPls version 6. The results of data processing and testing stated that all research hypotheses were acceptable. Acceptance of the hypothesis is the basis for researchers to draw conclusions that emotional intelligence variables and career adaptability variables are positive and significant shapers for achievement motivation, emotional intelligence variables are positive and significant shapers for career adaptability, career adaptability variables are a partial mediation in the relationship between emotional intelligence and achievement motivation in generation Z students in West Kalimantan when facing face-to-face lectures after the COVID-19 pandemic.